Human Factors in Health(care) Informatics: Toward Continuous Sociotechnical System Design - CARAYON, Pascale (Stud Health Technol Inform, 2019)
Developing structures and processes for continuous sociotechnical system design is key to sustaining human factors (HF) knowledge in the context of rapid health care changes and technological innovations. Two research studies illustrate how to embed HF in organizational learning processes and structures. We need to develop innovative HF methods for continuous sociotechnical system design.